Pengaruh Kompetensi, Budaya Organisasi Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada PT PAG - Permana, Buyung Satria; Marbawi, Marbawi; Qamarius, Ibrahim (Universitas Malikussaleh, 2020)
Abstract: This study aims to determine the influence of competence and organizational culture through organization commitmen and its impact on employee performance to the PT. Perta Arun Gas of Lhokseumawe Regency. The data used is primary data by distributing questionnaires to 67 employees of the PT. Perta Arun Gas of Lhokseumawe Regency. Data analysis method used is path analysis and processed with the help of Statistical Package for Social Science (SPSS) application program. The result of the research shows that there is influence of competence and organizational culture to organization commitmen, and there is also influence of competence and organizational commitment toward employee performance, however organization culture is not influuence of employee performan PT. Perta Arun Gas of Lhokseumawe Regency. Furthermore, the results of the study found that organization commitmen variables mediate the absolute (full mediation) relationship of competence to the employee performance at the PT. Perta Arun Gas of Lhokseumawe Regency. Keywords : Competence, Organization Culture, Organizational Commitment and Employee Performance.